The association of systemic lupus erythematosus and myasthenia gravis. - Vaiopoulos, G. (BMJ Group, 1994)
Two women with the rare association of systemic lupus erythematosus (SLE) and myasthenia gravis (MG) are reported. The first patient developed SLE (arthritis, severe thymectomy for MG. The second patient developed SLE (oral ulcers, arthritis, serositis, leukopenia, high titres of anti-DNA and anti-nuclear antibodies) 4 years prior to the clinical and serological onset of MG. Lymphocyte subsets and in vitro proliferative responses of peripheral blood mononuclear cells to mitogens were normal in both patients. A review of the literature revealed 26 additional patients with definite SLE coexisting with MG. Besides the theoretical interest of this association, the differential diagnosis of fatigue in patients with SLE should always include the possibility of MG.